Stress testing in banking sector and its interpretation - Palme, Vít (2015)
This bachelor thesis focuses primarily on stress testing in the banking sector. It has two major purposes. The aim of first two chapters is to provide a solid overview of stress testing methodologies, core principles and issues as well as most relevant bank risks in hope of contributing to better understanding why are stress tests used and becoming ever more popular. The final, third chapter discusses the concept of a leverage ratio in general and further assesses the leverage ratio newly introduced as a supplementary tool to already existing risk-weighted capital requirements in Basel III. I conclude that a leverage ratio is a vital part of regulatory framework, even though the way it is designed is Basel III has some flaws.